Short-term preoperative nutritional intervention for cleft lip and/or palate surgery eligibility: an effectiveness evaluation in six countries. Issue 1 (March 2021) - Said, Shady; Chattopadhyay, Lily; DiBona, Melissa; Steppling, Charlotte; Kwadjo, Dede; Ramamonjisoa, Mamy; Gallardo, Wendy; Almenfarez, Fatima; Rosales, Samanta; Nthalika, Ibrahim; Magee, William; Auslander, Allyn
Abstract: Background: Children with cleft lip and/or palate (CL/P) are highly susceptible to malnutrition, which can restrict their ability to receive safe surgery. Ready-to-use therapeutic foods (RUTF) are an effective treatment for children with malnutrition; however, the effectiveness of short-term nutritional supplementation in preparing patients for cleft surgery has not been demonstrated. We studied the effectiveness of RUTF in transitioning malnourished patients with CL/P, who were initially ineligible for surgery, into surgical candidates. Methods: A cohort of patients with CL/P who were initially deemed ineligible for surgery due to malnutrition from Ghana, Honduras, Malawi, Madagascar, Nicaragua, and Venezuela was followed by Operation Smile. Patients were enrolled in a nutrition program that provided RUTF packets and tracked age, weight, and height at each visit. A WHO Z score was calculated for each patient to longitudinally track malnutrition status. Patients were considered eligible for surgery when their Z scores were in the normal range (Z>–1). The study was part of a collaborative programme between Operation Smile (NGO), Birdsong Peanuts (peanut shellers and distributors), and MANA Nutrition (RUTF producer). Findings: 556 patients were recruited between June, 2017, and January, 2020. Initially, 28·2% (n=157) were diagnosed with severe malnutrition, 21·0% (n=117) with moderate malnutrition, and 50·7% (n=282) with mild malnutrition. Most patients (325 [66·4%]) presented for at least one return visit. Of patients who returned, 207 (56·1%) became eligible for surgery; 32 (15·5%) initially with severe malnutrition, 30 (14·5%) with moderate malnutrition, and 145 (70·0%) with mild malnutrition. By the second visit, the mean Z score increased significantly from −2·5 (moderate malnutrition) to −1·7 (mild malnutrition) (p<0·001). Mean time to attain surgical eligibility from enrolment was 6 weeks (range 1–103 weeks). There was a significant difference in the proportion of patients who became eligible by country (p<0·001). Interpretation: Malnutrition prevents many children with CL/P in low-income and middle-income countries from receiving surgical care, even when provided for free, creating a larger disparity in access to surgery. In an average of 6 weeks with an approximate cost of US $30 per patient, RUTF transitioned over half of these patients into safe surgical candidates, making it an effective short-term preoperative nutritional intervention. Through unique partnerships, the expansion of cost-effective, large-scale nutrition programmes can play a pivotal role in ensuring those at the highest risk of living with unrepaired CL/P receive timely and safe surgical care. Funding: Birdsong Peanuts.